Understanding Teacher Evaluation in Finland: A Professional Development Framework - Tarhan H; Karaman C; Kemppinen L; Aerila JA (EDITH COWAN UNIV, 2022)
This study explores the characteristics of the teacher evaluation model in Finland. Highlighting the unique qualities of the Finnish case, we also compare these teacher evaluation practices with the increasingly applied value-added model (VAM) for teacher evaluation across the globe. Our analysis revealed that the Finnish Model prioritises teacher empowerment and professional development by carrying out bottom-up evaluation practices. With a clear focus on teacher empowerment and professional development, this framework substantially differs from accountability measures such as VAM, which emphasize rigid data collection procedures and the use of standardized test scores to hold teachers accountable based on their students' academic performance. This study also revealed that professional development endeavours of teachers are highlighted as the key elements in Finnish teacher evaluation. Ongoing needs analyses for professional development also form the basis for assessing teachers in Finland.